Obesity management in primary care: Are we adequately preparing the next generation of Canadian family physicians? - Piccinini-Vallis, Helena; Evdaev, Vlad; Asaminew, Joseph; McCurdy, Therese; Rogers, Mark; Vallis, Michael (Obesity Pillars (Online), 2024)
Obesity is a chronic disease that affects a large proportion of the population. We examined the preparation of Canadian medical learners for obesity management through three cross-sectional studies exploring the: 1) knowledge of evidence-based obesity management among medical students; 2) perspectives of family medicine residents on the adequacy of obesity management training in their residency programs; and 3) intentions of family medicine residents regarding obesity management when they enter practice. An online survey instrument was developed for each study. For Study 1, the survey was developed by HP, VE and JA; the questions mapped onto the ten domains outlined in the 2020 Canadian Clinical Practice Guidelines on the Management of Obesity in Adults. For Study 2, the survey was developed by HP and TMcC; the questions aligned with competencies in the management of other chronic diseases. For Study 3, the survey was developed by MR, HP and MV; the Capability, Opportunity, and Motivation (COM-B) model was used as a framework for the questions. All three surveys met the criterion for face validity and the survey for Study 3 met criteria for content and criterion validity. Study 1 enrolled 26 first-year and 22 fourth-year students. Total correct scores were below 50 % for both groups, and patient-centeredness scores differed significantly between the groups. Study 2 enrolled 494 family medicine residents; less than 25 % thought there was sufficient time devoted to training in obesity management during residency and approximately 75 % experienced inconsistent messaging about obesity management from their preceptors. Study 3 enrolled 150 family medicine residents. Few participants believed that they had been well trained or had a clear plan for managing obesity, but most believed that obesity management will form part of their practice and that they will have the time and resources for obesity management. Current medical education does not reflect the requisite knowledge for contemporary obesity management. Further, family medicine residents identified gaps in mentorship of contemporary principles of obesity management. These findings support the revision of the medical curriculum in Canada to better reflect the science of obesity and its management. [Display omitted]